Evaluation of cytotoxic, DNA protecting and LPS induced MMP-9 down regulation activities of Plectranthus amboinicus (Lour) Spreng. essential oil. - Thirugnanasampandan, R.; Ramya, G.; Gogulramnath, M.; Rajarajeswaran, J.; Kanthimathi, M.S. (Emanuscript Services, 2014)
Introduction: Plectranthus amboinicus(Lour) Spreng is a known medicinal plant used in Siddha and Ayurveda medicines in India. It has enormous medicinal potential to treat various diseases. Methods: The present study focused on the use of essential oil obtained from the leaves of Plectranthus amboinicus to test cytotoxicity against breast (MCF-7) and colorectal (HT-29) cancer cell lines, to protect DNA from H2O2 induced genotoxicity through comet assay and to treat inflammation in lipopolysaccharide (LPS) induced over expression of matrix metalloproteinase-9 (MMP-9) in human peripheral blood mononuclear cells (PBMCs) by gelatin zymogram and inhibition at transcriptional level confirmed using RT-PCR (reverse transcriptase polymerase chain reaction). Results: Cytotoxicity of essential oil against MCF-7 and HT-29 cancer cell lines revealed the IC50 values of 53±0.01 and 87±0.01μg/mL respectively. At 200μg/mL essential oil protected against 75% of DNA damage in 3T3-L1 fibroblast cells. Essential oil showed significant reduction in production of MMP-9 in a concentration dependent manner. Conclusion: Overall, the results showed that essential oil of P. amboinicus is a potent bioactive substance and it could be used in herbal medicine preparations.